Epidemiology of Invasive Fungal Infections at Two Tertiary Care Neonatal Intensive Care Units Over a 12-Year Period (2000-2011) - Roshani R. Agarwal MD; Rajkumar L. Agarwal MD; Xinguang Chen MD, PhD; Jorge L. Lua MD; Jocelyn Y. Ang MD (SAGE Publishing, 2017)
We conducted a retrospective review of 168 patients with invasive fungal infections from January 2000 to December 2011 in 2 neonatal intensive care units. Patients with Candida bloodstream infection (BSI, n = 152) were further analyzed. C albicans was the most common species overall (47%); however, there was an increase in non- albicans sp from 2006 to 2011. Candida BSI clearance rates were lower in extremely low birth weight infants (77% vs 93%, P = .01) and in patients with C albicans infections (77% vs 91%, P = .01). Clearance rates improved from 2000 to 2005 (70% - 90%) to 2006 to 2011 (86% -100%). Combination antifungal use increased during the later years (73% vs 49%, P < .05) and in patients with end-organ dissemination (83% vs 54%, P < .05). We concluded that extremely low birth weight infants and C albicans infection are factors associated with nonclearance of Candida BSI. Successful clearance of Candida BSI improved in 2006 to 2011, perhaps due to increase in non- albicans species and the use of combination antifungals.